Triple therapy with pravastatin, low molecular weight heparin and low dose aspirin improves placental haemodynamics and pregnancy outcomes in obstetric antiphospholipid syndrome in mice and women through a nitric oxide-dependent mechanism - Eleftheria Lefkou (17052414) (2020)
Objectives A previous pilot study showed that pravastatin supplementation improved pregnancy outcomes in women with obstetric antiphospholipid syndrome (OAPS) that developed placental insufficiency despite standard of care treatment low molecular weight heparin plus low dose aspirin (LMWH + LDA). In this study we investigated the mechanism behind the beneficial effects of the triple therapy LMWH + LDA + pravastatin in improving uteroplacental vascular function and reducing pregnancy complications in OAPS. We hypothesized that nitric oxide (NO) is involved in the vasculoprotective effects of the triple therapy. A mouse model of OAPS that resembles the clinical scenario was used to test this hypothesis. Methods Eleven women with OAPS that developed preeclampsia (PE) and/or intrauterine growth restriction (IUGR) associated with uteroplacental vascular dysfunction despite treatment with LMWH + LDA participated in this study after given informed written consent. Seven women were supplemented with pravastatin at the time abnormal uterine artery Dopplers were detected and 4 remained on LMWH + LDA treatment only. Wire myography was used to identify the mechanisms underpinning the protective effects of the triple therapy in the mouse model of OAPS. Results The triple therapy increased serum NO levels, diminished uteroplacental vessels resistance improving placental function and prolonged pregnancies compared to conventional treatment LMWH + LDA, leading to live births in women with OAPS. Comparable to the observations in women, the triple therapy protected pregnancies in OAPS-mice, increasing placental perfusion and pregnancy outcomes. A synergistic vasculoprotective effect of the triple therapy on uterine arteries and aorta was demonstrated in OAPS-mice. LMWH + LDA showed a partial protection on endothelial function. Addition of pravastatin increase eNOS synthesis, expression and activity/signaling leading to a significant increment in nitric oxide (NO) generation, resulting in improved placental vascular function and total protection of pregnancies. Conclusion LMWH + LDA + PRAV increased serum NO levels and significantly improved placental haemodynamics and maternal and neonatal outcomes in women and mice with OAPS. A role for eNOS/NO in mediating the placental vasculoprotective effects in OAPS-mice was demonstrated, strengthening the concept that impaired NO production is a crucial mediator in the pathogenesis of OAPS and a potential target for pharmacological interventions. The efficacy of pravastatin supplementation should be confirmed in a larger clinical trial. Other Information Published in: Biochemical Pharmacology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.bcp.2020.114217